Análisis del código orgánico general de procesos en lo relacionado a la obligatoriedad de realizar prácticas pre profesionales de los egresados de las carreras de derecho; propuesta de reforma. - Castillo Alvarez, Leonides Justino (2010)
It corresponds as part of the thesis plan structure starting with the approach of the matrix problem, fearing first component as the delimitation of the problem that will be studied during the course of the development and implementation of legal research. Precisely to meet the above I have located in the revision of rules of singular importance as indeed is the general organic code processes (COGEP), in force since May 22 this year and published in the Supplement to Official Gazette no. 506, noting that the problem I try and corresponds to the reform that incorporates the organic COGEP judicial function code took effect from the date of publication referred to above. A second obstacle to my approach is that pre professional practices can only be carried out in public institutions that have an agreement with the council of the judiciary, denying the possibility that they may be made in legal clinics free exercise of lawyers in private companies or other non-governmental organizations with social object and purpose; Finally I consider the most serious graduate law degree injury is that it must wait for the judicial council through the Sub Directorate of pre Internships allocated quotas for the placement after the opening of the courses which they are held twice a year, which primarily represents a risk in the sense that the large number of graduates nationwide, no institutional coverage for practitioners, and then of course because this process presupposes procrastination and delay for graduates to obtain his law degree, because it was not considered the situational status of students of distance learning mode like mine, which involves a limitation that can frustrate aspirations, by reason that for practice on a regular schedule, students must necessarily give up their jobs, as the licensing or permits in the public or private sector involve risk of losing their jobs, thus generating an obvious injury as it is impossible for graduates to graduate without previously been declared fit professionally by the Judicial Council, a situation that once it has fulfilled its pre professional practices cycle occurs